Peruvian health and gastronomy under a social, economic and competitive perspective - Ismael San Mauro Martin (2019)
Objective: In Peru, health and food sectors are related economically and socially. We aimed todemonstrate which are the opportunities and challenges of Peruvians food sector in relation to humanhealthcare sector, from where future decisions may be taken; and promote Technology and TechnologicalInnovation with scientific rigor in that sector. Method: Recognize and analyze holistically the health andfood sectors. Results: Their relationship has been demonstrated, as well as gaps in competitivenessand Science, Technology and Technological Innovation have been identified. Conclusion: Innovationin the field of Peruvian food sector, with a scientific rigor on behalf of population health is needed. Wepropose the implementation of a Science, Technology and Technological Innovation platform with theaim of standardizing the quality of traditional cuisine and developing gastronomy in Peru.